Financing Wind Energy under the EU Green Bond Standard : What Counts as an Environmentally Sustainable Investment? - Peltoniemi, Essi (My University, 2022)
This thesis examines the upcoming EU green bond standard and especially its connections to the EU taxonomy’s criteria relating to environmental sustainability in the context of wind energy. The aim is to interpret, systematize and apply the taxonomy criteria in wind energy projects and thus draw practical interpretation recommendations for green bond issuers and reviewers. By considering the taxonomy criteria in practice, certain conclusions can be made about the sustainability framing that the EU taxonomy has adopted. The thesis belongs to the practical doctrinal study of law and applies a methodological pluralism approach because of the instrumentalist rationality of the research subject. The pluralism approach also contributes to the applied doctrine of source of law, which here is dynamic. Further, using wind energy as the context of the thesis allows a deeper legal scrutiny and generates more concrete and sharpened conclusions about environmental sustainability. Hence, there are some connections also to the law in context approach. It was found that the taxonomy criteria relating to environmental sustainability must be interpreted in a context and process-based approach. Thus, individual circumstances must be considered which leaves discretion to the taxonomy users and may weaken the consistent use of EU taxonomy. The thesis identifies certain legal principles relevant to the EU taxonomy which could be used as interpretation tools to increase consistency, especially in tricky cases. Further, the main principle is that the taxonomy criteria must be met only on the activity or project level. This could allow green bond issuers to cherry-pick between different projects and create a falsely sustainable image. When considering the taxonomy criteria in practice, it was also noticed that sustainability framing of the EU taxonomy is rather economical, which, however, in the case of wind energy seems justifiable.
Keywords: sustainable finance, green bonds, EU green bond standard, EU taxonomy, environmental sustainability, wind energy